Drivers of Customer Satisfaction and Loyalty in The Coffee Shop Industry: Evidence from Fore Coffee - Putra , Marcel Valentino; Ellitan, Lena (Program MM Universitas Surabaya, 2026)
Purpose: The rapid growth of Indonesia’s contemporary coffee industry, particularly in Surabaya, has intensified competition among coffee brands. As a prominent market player, Fore Coffee faces increasing challenges in maintaining customer satisfaction and loyalty amid the abundance of alternatives and aggressive promotional strategies employed by competitors. This study aims to examine the influence of advertising, brand image, and product quality on customer satisfaction, as well as the subsequent effect of customer satisfaction on customer loyalty toward Fore Coffee in Surabaya. Method: A quantitative research approach was employed, with data collected through questionnaires distributed to respondents who met the following criteria: residents of Surabaya, aged 17 years or older, who had purchased Fore Coffee within the past month and had been exposed to its advertisements. A total of 224 valid responses were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3.0. The analysis included evaluations of both the outer model (validity and reliability testing) and the inner model (hypothesis testing). Result: The findings reveal that advertising, brand image, and product quality each have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction significantly influences customer loyalty. Among the independent variables, product quality and brand image exert stronger effects on customer loyalty compared to advertising. These results highlight the importance of maintaining consistent product quality, using high-quality ingredients, and establishing a modern and credible brand image to foster long-term customer loyalty.